2023
DOI: 10.3389/fpubh.2023.1043969
|View full text |Cite
|
Sign up to set email alerts
|

The impact of grandchild care on depressive symptoms of grandparents in China: The mediating effects of generational support from children

Abstract: ObjectivesDespite extensive studies about the direct effect of grandchild care on caregiver depression in China, understanding of its internal influencing mechanism has been limited. After controlling for socioeconomic factors, this study investigated whether the experience of caring for grandchildren had a long-term impact on the depression levels of grandparents, either directly or indirectly through generational support from adult children.MethodsThe subjects of this study were a total of 9,219 adults over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…It appeared that these articles used data from other countries in the early 20th century, while our findings emphasized that in recent China there seemed to be no extra mental benefit of longterm intensive care for grandparents. Against the background of modernity, Chinese young grandparents, on the one hand, maintain a certain degree of emotional need in intergenerational interaction and, on the other hand, gradually acquire the characteristics of independence (47). The youngest grandparents (i.e., from 45 to 69 years old) received the most benefits of stopping and reducing the intensity of care, while the older grandparents did not (see Supplementary Table S4), which supported our interpretation to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that these articles used data from other countries in the early 20th century, while our findings emphasized that in recent China there seemed to be no extra mental benefit of longterm intensive care for grandparents. Against the background of modernity, Chinese young grandparents, on the one hand, maintain a certain degree of emotional need in intergenerational interaction and, on the other hand, gradually acquire the characteristics of independence (47). The youngest grandparents (i.e., from 45 to 69 years old) received the most benefits of stopping and reducing the intensity of care, while the older grandparents did not (see Supplementary Table S4), which supported our interpretation to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that utilized longitudinal data involving 9,219 adults over 45 years [ 35 ] showed that caring for grandchildren positively correlates with better mental well-being among Chinese grandparents. Portions of the findings further revealed that children's support significantly mediates the impact of parenting experience on grandparents' mental well-being.…”
Section: Literature Reviewmentioning
confidence: 99%